2015
DOI: 10.1016/j.sbi.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of large macromolecular complexes

Abstract: Connecting dynamics to structural data from diverse experimental sources, molecular dynamics simulations permit the exploration of biological phenomena in unparalleled detail. Advances in simulations are moving the atomic resolution descriptions of biological systems into the million-to-billion atom regime, in which numerous cell functions reside. In this opinion, we review the progress, driven by large-scale molecular dynamics simulations, in the study of viruses, ribosomes, bioenergetic systems, and other di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
300
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 387 publications
(311 citation statements)
references
References 105 publications
2
300
0
2
Order By: Relevance
“…To build an accurate atomic model of the human 26S proteasome, we followed the strategy established for large macromolecular complexes (27,28). We first built comparative models of the human 26S proteasome subunits, extended template-free segments by de novo modeling, and superposed these human subunit models onto their respective yeast homologs.…”
Section: Resultsmentioning
confidence: 99%
“…To build an accurate atomic model of the human 26S proteasome, we followed the strategy established for large macromolecular complexes (27,28). We first built comparative models of the human 26S proteasome subunits, extended template-free segments by de novo modeling, and superposed these human subunit models onto their respective yeast homologs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in order to simulate larger systems, hybrid approaches [12,[57][58][59] must be followed. In such a method, a small region of interest is simulated with ab initio molecular dynamics, while the rest of the molecular system is approximated with molecular mechanics:…”
Section: Hybrid Quantum Mechanics-molecular Dynamics Methodsmentioning
confidence: 99%
“…Especially under crowding conditions, membrane dynamics slow down, and sampling of the motions of individual membrane proteins -let alone of protein complexes -becomes a serious issue (Goose and Sansom, 2013;Javanainen et al, 2013). The use of massively parallel computer resources or dedicated hardware can extend the range of applicability of all-atom models to a certain extent (Perilla et al, 2015). For instance, short all-atom simulations of an entire organelle (Chandler et al, 2014) or all-atom simulations totalling over 100 μs of a G-protein-coupled receptor (GPCR) embedded in a small lipid membrane patch (Dror et al, 2011) have in fact been reported, but these are associated with a computational cost that is not available to everyone.…”
Section: Atomic Resolutionmentioning
confidence: 99%